Unilateral absence of the lunate sulcus: an anatomical perspective. - Srijit, D.; Shipra, P. (2008)
The present study examines the gross anatomical features of anomalous lunate sulcus detected incidentally in a cadaveric brain and discusses its clinical importance. The absence of lunate sulcus was carefully studied in a dissected brain specimen. The absence of lunate sulcus was observed unilaterally on the right side of a cadaveric brain specimen. The lunate sulcus was clearly appreciated on the left side whilst on the right side it was absent. The right hemisphere of the cerebellum was also bigger in size as compared to the left. The absence of lunate sulcus is a rare finding, which may be detected incidentally. The anatomical knowledge of the lunate sulcus may be important for neurosurgeons operating on the occipital lobe and the radiologists interpreting CT scan.